Tinjauan Kebutuhan Air Bersih dan Pendistribusiannya pada Desa Lohiatala (Bagian Atas), Kecamatan Kairatu Barat, Kabupaten Seram Bagian Barat: Review of Clean Water Needs and its Distribution in Lohiatala Village (Upper Part), Kairatu Barat District, West Seram Regency - Apriyanti, Fani; Serang, Rudi; Pattiselanno, Steanly R. R. (Litera Academica Publishing, 2025)
Water is the most essential resource in life. In every activity of life, not only humans but all living beings need water. The issue of clean water availability is something important that cannot be separated from the fabric of life. In Lohiatala village, the water source is taken from the river, then pumped to the upper settlement and stored in reservoirs, followed by distribution to distribution tanks and dispersed through 6 faucet points scattered throughout the village. This research aims to determine the population and clean water needs until the year 2043. In the research, the need for clean water in the village of Lohiatala is predicted using a population projection calculation method with an arithmetic approach, estimating a population of 782 people by 2043. Based on this population number, the required amount of water in the village of Lohiatala is 14,097 liters per hour or 0.00391 m³/second. To optimize the distribution of clean water, it is necessary to calculate the pipe diameter from the distribution tank to the sixth faucet; the result obtained by the researchers is 10 inches (taken from the calculation of the largest pipe diameter).